A new species of Placospongia Gray, 1867 (Porifera, Demospongiae, Placospongiidae) and new record of P. ruetzleri van Soest, 2017 from Northeast, Brazil - Mácola, Rosa; Menegola, Carla (Zootaxa, 2021)
A new species of Placospongia is described from Bahia State, Brazil. Placospongia giseleae sp. nov.. The specimen is found on the underside of rocks in shallow waters (0-20m), and is unique by having a spiculation consisting of two tylostyle categories, selenasters and acanthomicrorhabds. In addition, Placospongia ruetzleri, is recorded for the first time to Bahia state, 2.974 km southwards from its type locality, the Guyana shelf. The diversity of Placospongia species is raised from two to four taxa. An identification key for Western Atlantic Placospongia species is presented.